Preparation and characterization of manganese-based and carbon-based nanomaterials for supercapasitors application - Gomaa Abdelgawad, Mohammed Ali (2015)
In this study, electrochemical materials, namely MnO2, reduced graphene oxide (rGO), porous carbon nanoparticles (PCNs), and rGO/MnO2 nanocomposite, were prepared in diverse morphologies such as nanoflowers (MnO2), nanosheets (rGO), and nanoparticles (carbon). Different physical and chemical characterizations have been conducted to study the structural and morphological properties of the materials under study. Electrochemical properties of the above materials have been studied comprehensively using cyclic voltammetry (CV), galvanostatic charge–discharge (CDC) and electrochemical impedance spectroscopy (EIS) in order to evaluate their suitability as an electrode for supercapacitive energy storage. MnO2 nanoflowers was recovered from spent batteries by a combining leaching and electrowinning techniques. The recovered MnO2 nanoflowers exhibited high specific capacitance (Cs) (303 F g-1 at 5 mV s-1). Furthermore, MnO2 was electrodeposited by potentiostatic and galvanostatic conditions. Under similar electrodeposition conditions, MnO2 deposited by galvanostatic condition showed smaller particle size, less compact layered structure and wider band gap compared to potentiostatic deposition. The galvanostatic MnO2 rendered facile ions diffusion, low resistances and showed superior capacitive behavior. The rGO nanosheets were prepared by hydrazine reduction of graphene oxide and their electrochemical properties were studied. The rGO showed high Cs of 191 and 168 F g-1 at 5 mV s-1, in 5 M KOH and 1 M Na2SO4, respectively and high cycling stability > 96 % over 1000 cycles. In addition, PCNs with fine particles size of 35 nm were prepared from oil palm leaves using a catalyst free process. The Cs of PCNs is 245 and 213 F g-1 at 5 mV s-1 in 5 M KOH and 1 M Na2SO4, respectively. The PCNs showed high cycling stability of 95 %. Practical supercapacitors were developed using rGO and PCNs; the devices delivered energy densities ~18 and ~25 W h kg-1 at power densities 340 and 360 W kg-1, respectively, under wider operating voltage window of 2 V in neutral electrolyte. rGO/MnO2 nanocomposite has been prepared by simultaneous electrochemical conversion of GO and Mn3O4. The Cs of rGO/MnO2 is 457 F g-1 at 5 mV s-1, which are several folds higher compared to those for pure rGO and MnO2. Furthermore, rGO/MnO2 showed high stability of 95 % over 2000 CDC cycles. Therefore, the present study identifies electrochemical materials with improved energy storage capabilities.